2015
DOI: 10.1093/asj/sju070
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors That Contribute to Upper Eyelid Ptosis: A Study of Identical Twins

Abstract: 3 Diagnostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The U.S. population is aging, 15 and studies have revealed a clear association between increasing age and ptosis incidence. [8][9][10] Contact lens wear, whether rigid or soft lenses, is another common factor that can lead to development of bilateral or unilateral acquired ptosis, [16][17][18][19][20] and patients are now wearing contact lenses for a greater part of their life span because of, for example, availability of multifocal contact lenses for presbyopia. Unilateral or asymmetric acquired ptosis may arise in patients wearing the same or different lenses bilaterally or in patients wearing lenses monocularly.…”
Section: Current State Of Ptosis Diagnosis and Treatmentmentioning
confidence: 99%
“…The U.S. population is aging, 15 and studies have revealed a clear association between increasing age and ptosis incidence. [8][9][10] Contact lens wear, whether rigid or soft lenses, is another common factor that can lead to development of bilateral or unilateral acquired ptosis, [16][17][18][19][20] and patients are now wearing contact lenses for a greater part of their life span because of, for example, availability of multifocal contact lenses for presbyopia. Unilateral or asymmetric acquired ptosis may arise in patients wearing the same or different lenses bilaterally or in patients wearing lenses monocularly.…”
Section: Current State Of Ptosis Diagnosis and Treatmentmentioning
confidence: 99%
“…Contact lens wear, which involves repeated manipulation of the eyelid, and therefore the potential risk of microtrauma to the levator aponeurosis, has also been associated with the development of acquired ptosis, with studies linking both hard and soft contact lens wear to increased incidence (Table 2 ) [ 25 29 ]. A retrospective analysis of 15 patients with ptosis attributable to contact lens wear revealed that all were hard lens wearers and 13 of 15 had been wearing their lenses for >17 years.…”
Section: Acquired Ptosis Risk Factorsmentioning
confidence: 99%
“…A retrospective analysis of 35 patients aged 18–50 years old presenting with ptosis in a hospital ophthalmology department found that 29 of the 35 patients had a history of either hard or soft contact wear (mean wear time 17.6 and 9 years, respectively) [ 26 ]. A broad analysis of environmental factors contributing to ptosis in 286 sets of adult twins (range: 18–82 years old) found a significant association between both hard and soft contact lens wear and ptosis, but no association with respect to other environmental factors evaluated, including BMI, smoking status, alcohol consumption, hours of sleep per night, or sun exposure [ 29 ]. Consistent with these individual studies, a systematic literature review found significant risk associated with both hard (odds ratio 17.38 (3.71–81.29)) and soft (odds ratio 8.12 (2.68–24.87)) contact lens wear [ 27 ].…”
Section: Acquired Ptosis Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies have suggested a potential association between blepharoptosis and general body condition, especially obesity [10][11][12][13]. These prior studies evaluated obesity using body mass index (BMI), waist circumference (WC), or body fat percentage, and demonstrated that obesity and blepharoptosis are positively associated [10].…”
Section: Introductionmentioning
confidence: 99%